Medium Optimization for Synaptobrevin Production Using Statistical Methods - Khalili, Ehsan; Khoshayand, Mohammad Reza; Abbasi, Ebrahim; Lakzaee, Mostafa; Parvizi, Mohammad Reza; Faramarzi, Mohammad Ali; Aminian, Mahdi; Nojoomi, Farshad (Archives of Medical Laboratory Sciences, 2019)
Background: Botulinum toxin, the most potent biological toxin, has become a powerful therapeutic tool for a growing number of clinical applications. Molecular studies have identified a family of synaptic vesicle-associated membrane proteins (VAMPs, also known as synaptobrevins) which have been implicated in synaptic vesicle docking and fusion with plasma membrane proteins. Materials and Methods: Using the synaptobrevin as a substrate for in vitro assay is the method to detect BoNT activity. We have been working on optimizations of bacterial expression conditions and media for high-level production of synaptobrevin peptide. Statistics-based experimental design was used to investigate the effect of medium components (E. coli strain, peptone, IPTG, yeast extract, ampicillin, and temperature) on synaptobrevin production by E. coli. Results: A 24 fractional factorial design with center points revealed that IPTG and temperature were the most significant factors, whereas the other factors were not important within the levels tested. This purpose was followed by a central composite design to develop a response surface for medium optimization. The optimum medium composition for synaptobrevin production was found to be: IPTG 29 mM, peptone 10 g/L, yeast extract 5 g/L, temperature 23°C and ampicillin 100 mg/L. This medium was projected to produce, theoretically, 115 mg/L synaptobrevin. Conclusion: The optimum medium composition synaptobrevin production was found to be: BL21 (E.coli strain), LB medium (peptone 10 g/L, Yeast 5 g/L), Ampicillin (100 mg/L), IPTG (0.29 mg/L) and temperature (23°C).